Improved design of universal-combined cultivator-fertilizer - Khudoyberdiev T.S.; Nurmatov Sh.N.; Boltaboev B.R; M.Sh.Kholdarov (International Journal on Orange Technologies, 2020)
In the cultivation of high yields of cotton, the role of agro-technical measures, including timely quality processing and deep softening between rows of cotton is very important. However, due to the lack of sectional cultivators currently used, it is not planned to aggregate it with a tractor and spend a lot of labor and time to install the necessary working bodies, as well as deep loosening of the soil. In order to solve the problem, the article presents the results of research on the development of a new universal-combined design of a suspended cultivator, which works between rows of cotton. The design of the proposed suspension universal-combined section cultivator-feeder is relatively simple, the cotton is processed and fertilized between the rows and deeply softened when necessary.